Monsignor Quixote - Greene, Graham, 1904-1991 (London : | Bodley Head, 1982)
When Father Quixote, a local priest of the Spanish village of El Toboso who claims ancestry to Cervantes' fictional Don Quixote, is elevated to the rank of monsignor through a clerical error, he sets out on a journey to Madrid to purchase purple socks appropriate to his new station. Accompanying him on his mission is his best friend, Sancho, the Communist ex-mayor of the village who argues politics and religion with Quixote and rescues him from the various troubles his innocence lands him. [By Publisher]